2013
DOI: 10.1111/jgh.12220
|View full text |Cite
|
Sign up to set email alerts
|

Update on epidemiology of hepatitis B and C in China

Abstract: A high rate of chronic hepatitis B virus (HBV) infection in China is mainly caused by perinatal or early childhood transmission. Administration of universal HBV vaccination in infants has led to a dramatic decrease in HBV epidemiology, with hepatitis B surface antigen (HBsAg) prevalence declining from 9.75% in 1992 to 7.18% in 2006. The major HBV genotypes are B and C, with B being more prevalent in the southern part and C more prevalent in the northern part of China. A national survey carried out in 1992 show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
252
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(266 citation statements)
references
References 32 publications
9
252
4
1
Order By: Relevance
“…Importantly, 36% of the participants did not know the mother to child route, but mother-to-child transmission is the leading cause of HBV infection in China. 17 HBV stigma was greatest in the fear of contagion domain. 12 We found that fear of being infected with HBV was significantly associated with rural migrant worker HBV-related discrimination (See Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, 36% of the participants did not know the mother to child route, but mother-to-child transmission is the leading cause of HBV infection in China. 17 HBV stigma was greatest in the fear of contagion domain. 12 We found that fear of being infected with HBV was significantly associated with rural migrant worker HBV-related discrimination (See Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Mother-to-child transmission is the leading cause of HBV infection in China. 29 We suggest that informing people that a significant proportion of infection is accounted for by mother-to-child transmission. This perspective might be helpful in reducing HBV-related discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…After 20 years, more than 200 counties had included the hepatitis B vaccine in their national infant immunization programs. These efforts resulted in a remarkable decrease in hepatitis B virus surface antigen (HBsAg) positivity in the population, especially in children and adolescents [5]. However, an epidemic survey revealed that 7.18% of the Chinese population was HBsAg positive, demonstrating that HBV infection was still a public health burden in China [5].…”
Section: Introductionmentioning
confidence: 99%
“…These efforts resulted in a remarkable decrease in hepatitis B virus surface antigen (HBsAg) positivity in the population, especially in children and adolescents [5]. However, an epidemic survey revealed that 7.18% of the Chinese population was HBsAg positive, demonstrating that HBV infection was still a public health burden in China [5]. According to previous studies, the higher rates of HBV infection could be detected in some specific groups, such as patients undergoing dialysis, parenteral drug users, immunosuppressed patients, and male homosexuals [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%